Identifying Students’ Phonological Errors in Pronouncing Vowel Diphthong at MAN 1 Pekanbaru - Hafifah Dwi Lestari; Rizky Gushendra (Indonesian Journal of Integrated English Language Teaching, 2022)
This research aimed to identify students’ phonological errors in pronouncing vowel diphthongs.Furthermore, the researcher also formulated the problem in a question, what kinds of voweldiphthong sound that is most frequently found errors in students’ pronunciation at tenth gradeMAN 1 Pekanbaru. The subject of this research was the tenth grade of MAN 1 Pekanbaru in theacademic year 2021/2022. This research used the descriptive quantitative method. The researcherrandomly selected 60 samples from 395 populations. The instrument of this was a pronunciationtest of the English Vowel Diphthong word containing 8 types of English Vowel Diphthong andfor each type, there are 2 focus words, and a voice recorder to record the students’ pronunciation.The result of the identification showed that the students made errors out of a total of 339 words.The kinds of errors on vowel diphthong sound which are most frequently found in students’pronunciation at tenth grade MAN 1 Pekanbaru are in Diphthong [ɔʊ] the focus word is “although”gets a total error of 72%. In Diphthong [ʊə] both focus words get the highest total error, which is“during” gets 65% and “obscure” get 62%. And the last Diphthong [aɪ] with the focus word is“sacrifice”, which gets a total error of 61%.